2015
DOI: 10.1371/journal.pone.0131098
|View full text |Cite
|
Sign up to set email alerts
|

A Benchmark Data Set to Evaluate the Illumination Robustness of Image Processing Algorithms for Object Segmentation and Classification

Abstract: Developers of image processing routines rely on benchmark data sets to give qualitative comparisons of new image analysis algorithms and pipelines. Such data sets need to include artifacts in order to occlude and distort the required information to be extracted from an image. Robustness, the quality of an algorithm related to the amount of distortion is often important. However, using available benchmark data sets an evaluation of illumination robustness is difficult or even not possible due to missing ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A benchmark data set ( https://sourceforge.net/projects/gait-cad/files/Benchmarks/hardware_items/ ) is specifically designed to conform to evaluation criteria that are most suitable for our methodology. A complete description of data set is given in [ 32 ]. It is based on 4 scenes r = 1, …, 4 containing solid objects i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A benchmark data set ( https://sourceforge.net/projects/gait-cad/files/Benchmarks/hardware_items/ ) is specifically designed to conform to evaluation criteria that are most suitable for our methodology. A complete description of data set is given in [ 32 ]. It is based on 4 scenes r = 1, …, 4 containing solid objects i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Measures based on a given ground truth previously used in [ 32 ] are segmentation measures ( q 1 and q 2 ) and a classification measure ( q 3 ). Segmentation measures penalize the difference between objects detected and the number of non-overlapping pixels with respect to the ground truth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that biological phenomena such as fluorescently labeled cell populations can be realistically simulated if enough knowledge of the investigated probes was available [5][6][7][8]. The charm of simulated data is the availability of a reliable ground truth and literally unrestricted possibilities to adjust parameters like noise levels, sampling rates or light attenuation, which can hardly be achieved by imaging dynamically changing organisms and thus prohibits robustness analyses as in [9]. Nevertheless, existing simulated benchmarks are often much simpler than the real application scenarios and mostly focus solely on a single processing step.…”
Section: Introductionmentioning
confidence: 99%